(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Acute cholecystitis is an extremely common surgical emergency, with gallbladder inflammation from mild to gangrenous forms. Early surgical intervention, often laparoscopic cholecystectomy, is required to minimize the chances of morbidity and to improve important patient outcomes. The introduction of laparoscopic services continuing 24/7 is designed to minimize surgical delays and improve care quality. Aim: The purposes of this study are to compare the safety and feasibility of laparoscopic cholecystectomy performed 24/7 for various grades of acute cholecystitis, ranging from mild to gangrenous. Methods: Four hundred patients diagnosed with acute cholecystitis were divided into three groups such as grade I (mild), grade II (moderate), and grade III (severe/gangrenous) according to the Tokyo Guidelines, and a comparative study was done. Patients were divided into two groups by simple fixed ratio allocation: one undergoing elective laparoscopic cholecystectomy during regular business hours (n = 200) or those who underwent 24/7 laparoscopic cholecystectomy (n = 200). Operative time, conversion rates to open surgery, complications rates, hospital stay duration and postoperative recovery metrics were assessed as outcomes. Chi-square tests were performed for categorical variables and t-tests for continuous variables, and a p value less than significant was taken as <0.05. Results: The elective group had a longer median hospital stay (5 days vs. 3 days, p<0.001) and higher complication rates than the 24/7 group (8% vs. 15%, p=0.02). There was no difference in conversion to open surgery in the two groups (5% vs. 6%, p=0.65). The 24/7 group had slightly longer operative times for Grade III cholecystitis (p = 0.04). There were no significant differences in postoperative recovery metrics. Results comparing 24/7 surgery versus surgery done only during normal operating hours did not differ meaningfully, except for subgroup analysis in Grade II cholecystitis, where 24/7 surgery resulted in lower inpatient mortality and morbidity. Color-coded tables of demographic distributions, bar graphs comparing complication rates, or pie charts clarifying the distribution of cholecystitis grades are graphical representations. Conclusion: Laparoscopic cholecystectomy can be safely implemented both selectively or as full implementation, around the clock, with no grade of acute cholecystitis excluding it. It also has been associated with decreased hospital stay and decreased complications without increasing conversion to open surgery. These findings indicate the benefits of around-the-clock laparoscopic services to improve acute cholecystitis patient outcomes.